A Synthesis of mixed evidences regarding role of Birth companionship on Labor Progression and maternal health: A Narrative review - Pushpa, Pushpa; Kumari, Kiran; Jangid, Jyoti; Anushiya, Anushiya (Universitas Andalas, 2025)
Childbirth can be a challenging experience, especially for first-time mothers. There are several methods are available to enhance the maternal and neonatal outcome. Continuous support from a chosen companion during labor significantly improves both maternal and neonatal outcomes. The literature search used PubMed, CINAHL, Ovid Medline and Scopus. Determination of keyword- which is based on PICOT framework, as follows P: Pregnant women, I: birth companionship, C: any comparison, O: Maternal & fetal outcomes, T: any time. The Article published in English, full text available article and published article were criteria for inclusion in this study. We reviewed eight papers of continuous support from a chosen companion during labor significantly improves both maternal and neonatal outcomes. This support includes emotional reassurance, pain management, physical comfort, and newborn care assistance. Studies indicate that such support also positively impacts postpartum mental health. The World Health Organization (WHO) and the Government of India recommend to have a birth companion for all women in labor. While there is still a gap in understanding how this support affects overall satisfaction studies show that non-medical support, such as from doulas, leads to better outcomes, including higher rates of vaginal births, reduced need for pain relief, and improved breastfeeding initiation. Despite challenges in implementation, continuous support is key to improving maternal and child health globally